Entrepreneurship: Tenacity, Future Self-Continuity, and Inter-Temporal Risky Choice - Zeng, Xueyun; Ouyang, Yuting (Frontiers in Psychology, 2020)
This study examines entrepreneurship. It focuses on the effect of tenacity and future self-continuity (FSC) on inter-temporal risky choice in the entrepreneurial context. A total of 129 Chinese undergraduates participated in this survey. The results formulate that tenacity positively correlates with the risky choices and inter-temporal risky choices, in which commitment, endurance, and challenge play a major role. Meanwhile, FSC predicts the risk-return of the subjects. Higher FSC corresponds to higher expected inter-temporal risk-return. Furthermore, the multivariable regression analysis shows that there is a reciprocal effect when tenacity and FSC work together on subjects’ inter-temporal risky decision-making. FSC slightly mitigates both the pursuit of risky-return and the tolerance of time delay for the subjects with high tenacity. This implies that their worthwhile goal is to seek smooth income rather than to pursue an extreme high risk-return. These findings extend the research on personality, choice, and entrepreneurship and provide a guiding significance to the start-up.